Sistem Pakar Diagnosa Vitiligo Menerapkan Metode Fuzzy Sugeno - Ricard Ricardo (STMIK Budi Darma, 2021)
Vitiligo is a disease that causes skin color to fade. Besides being able to attack any skin area on the body, this fading can also occur on the inside of the mouth, eyes, and hair. For the general public, to find out a diagnosis of vitiligo, you must consult an expert who is an expert in the diagnosis of this disease. However, the problem that often occurs is the inefficient use of time for experts to serve many patients for consultations so that it is difficult to handle patient problems in an efficient time. So that we need an application that can help, namely an expert system. An expert system is a computer program that contains knowledge from one or more human experts regarding a specific field. Expert systems can solve problems in accordance with the knowledge of an expert that is entered into the system. Expert systems in general are often used to carry out activities to diagnose a problem that only an expert can solve. Fuzzy Sugeno is a method that can be used to obtain the results of a diagnosis on an expert system. The stages of the Sugeno fuzzy method are the formation of fuzzy sets applying the implication function (rules). Rule composition, obtained from a data set of relationships between rules. Defuzzification, the input of defuzzification is a constant or linear equation.